DESIGN OF ETHNOMATHEMATICS-BASED LEARNING TOOLS VIEWED FROM AN ISLAMIC CULTURAL PERSPECTIVE (CASE STUDY: ISLAMIC BOARDINGSCHOOLS IN CIREBON-INDONESIA AND PENANG-MALAYSIA) - Iyay Robia Khaerudin; Herri Sulaiman; Muhammad Riyad Ariwibowo (Cirebon International Conference on Education and Economics Proceeding, 2024)
Learning tools are an important element in teaching and learning in the classroom. Educators should have their own learning tools to be more professional and systematic when teaching. Ethnomathematics-based learning tools are unique and have strengths that can be studied more deeply in this research. The combination of culture-based learning combined with contextual or realistic discoveries of Mathematics concepts makes it a very different field of study and has its own study for students' knowledge. The strong Islamic culture in the Cirebon region creates great potential in creating unique learning device designs that have strong character to develop students' character education. Likewise, the education system in Malaysia is Islamic-based. Of course, teaching and learning activities in schools must require a learning device design that is adapted to the Islamic culture that exists there. This gap is what makes it suitable between the two countries to conduct international collaborative research between schools in Cirebon and in Malaysia. The ethnomathematics context that will be studied is the discovery of ethnomathematics concepts in the Ancient Gamel Mosque in Gamel village, Plered, Cirebon Regency and the discovery of ethnomathematics concepts in the relics of Sunan Kalijaga in Cirebon City. These two places are sufficient for designing ethnomathematics-based learning tools with an Islamic cultural perspective which will later be tested in two countries, namely Cirebon and Malaysia. The design of the learning tools in question starts from the syllabus, curriculum, lesson plans and assessment rubrics. Thus, this study can design this learning tool and at the same time try it out at two boarding schools in Cirebon and Malaysia. Thus, the research data obtained is the result of distributing questionnaires, interviews and tests to subjects, namely junior high school level students (quantitative in nature).